Strategi Komunikasi Pemasaran PT Sinar Sosro Gunung Slamat dalam Mempertahankan Eksistensi Merek di Era Digital - Zephaniah, Gracia; Rr. Renny Soelistiyowaty (CV. ULIL ALBAB CORP, 2025)
The digital era encourages companies to continue innovating their marketing communication strategies so they can compete and maintain their brand presence. PT Sinar Sosro Gunung Slamat addresses these challenges by implementing a digital marketing approach tailored to each of its brands' characteristics and needs. This research uses a descriptive qualitative method to explain in depth how marketers implement and optimize marketing communication strategies to maintain brand position in the market. Data was collected through direct observation, active participation in marketing activities, in-depth interviews with relevant parties, and literature studies to support the analysis. The effectiveness of the marketing communication strategy is measured using several key performance indicators, such as the engagement rate, click-through rate, and cost per view. These indicators illustrate how well the content attracts and influences the audience. The company's ability to adapt, maintain consistent messaging across various platforms, and build customer loyalty through quick responses and personalized approaches were notable. The results of this study show how important it is to combine digital technology, targeted marketing strategies, and a deep understanding of audience behavior to create relevant and efficient marketing communications.